Analysis of The Principle of Fairness on The Validity of Consumer Consent in Telemarketing Agreements in The Banking Sector in Indonesia - Saiful Ahmad, Ahluddin; Pamadya Astuti, Yuniar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines the validity of consumer consent in banking telemarketing agreements through the approach of fairness theory and modern contract law doctrine. The analysis shows that telemarketing communication patterns create an information imbalance that affects the quality of verbal consent, so that the elements of agreement as stated in Article 1320 of the Civil Code are not substantively formed. This study also confirms that not providing consumers with copies of recorded conversations or written contracts weakens the evidence, reduces the effectiveness of the cooling-off mechanism, and contradicts the principles of consumer protection in the Consumer Protection Law (UUPK), the Electronic Information and Transactions Law (UU ITE), and POJK 6/2022. This study proposes the obligation to provide recordings, written contracts, and supporting documents as a mechanism to restore balance and ensure fairness in the formation of telemarketing agreements.